Pengembangan teknologi pengendalian hama utama kacang hijau menggunakan biopestisida - Yusmani Prayogo; Marida Santi Yudha Ika Bayu (Jurnal Entomologi Indonesia, 2020)
Pests are one of the main obstacles in improving mungbean production in Indonesia. Currently, conventional control by using synthetic pesticides is less successful because the population and damage due to the organism are still high. This study aims to evaluate the mungbean pest control technology by using biopesticide. The experiment was conducted using randomized block design, five treatments and five replicates. The treatments were P1: preventive of neem seed powder (NSP), entompothogenic virus which contain Spodoptera litura nuclear polyhedrosis virus (Virgra), and conidia of entomopathogenic fungi Beauveria bassiana (BeBas) application; P2: SBM, Virgra, and BeBas application based on economic threshold (ET); P3: application of synthetic pesticides based on schedule; P4: application of synthetic pesticides based on ET; and P5: without control. The results showed that the pests were armyworm (Spodoptera litura (Fabricius)), whitefly (Bemisia tabaci (Gennadius)), Empoasca sp., Megalurothrips usitatus (Bagnall), brown stink bug (Riptortus linearis (Fabricius)), green stink bug (Nezara viridula (Linnaeus)), and pod borer (Maruca testulalis (Geyer)). The application of NSP, Virgra, and BeBas, as preventive measures and the application of synthetic pesticides based on schedule effectively were suppressed pest population. In contrast, the application of biopesticides and synthetic pesticides based on ET did not suppress the development of major pests. The application of biopesticide based on ET are safe for the survival of natural enemies. Meanwhile, the application of synthetic pesticides can destroy existing natural enemies. Integrated management of NSP, Virgra, and BeBas, that are applied preventively are potential to be innovative technology for controlling the major mungbean pest to replace synthetic pesticides.